Safety of machinery - safety-related parts of control systems : - International Organization for Standardization
This part of ISO 13849-1 provides safety requirements and guidance on the principles for the desing and integration of safety-related parts of control systems (SRP/CS), including the desing of software. For these parts of SRP/CS, it specifies characteristics that include the performance level required for carrying out safety functions. It applies to SRP/CS, regardless of the type of technology and energy used (electrical, hydraulic, pneumatic, machanical, etc), for all kinds of machinery